Edmodo as Media to Support the Plumbing Theory Courses in Vocational Education Learning - Ramadhan, M. Agphin; Daryati, Daryati (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The purpose of the study was to determine the effectiveness of edmodos e-learning as supporting learning in the Plumbing Theory course in Vocational Education of Building Construction students. The research was conducted as the application of blended learning that carried out in an integrated manner at the Faculty of Engineering in 2019. The research method used the Quasy Experiment Method. Data collection techniques used were using multiple choice tests and questionnaires. The results of the research showed that Edmodo has been proven effective improve student learning outcomes of participants in the Plumbing Theory course. The post test results showed a significant increase after students were given treatment in the form of Edmodo utilization compared to the pre-test results that had not been given treatment. Edmodo has been proven to increase the learning motivation of students in the plumbing theory course. Edmodo has an advantage in its ease of access. Students participating in the Plumbing Theory courses access Edmodo with high intensity because it utilizes Edmodo in learning. The biggest obstacle experienced by students in accessing Edmodo is the internet network that does not support.